2019
DOI: 10.3390/ijerph16101836
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LGR-5 as a Predictor of Poor Outcome in Patients with Hepatocellular Carcinoma

Abstract: Hepatocarcinogenesis and distant metastasis pose major challenges for physicians. They are regulated by several genes, such as AKT, JUK, Wnt, and P53, and their expression activates several important processes such as cell proliferation, migration, motility, and interaction in the microenvironment. The leucine-rich repeat-containing G-protein-coupled receptor 5 (LGR-5) is a novel biomarker, particularly in stem cells, and is involved in embryogenesis, tumor development, and tumor cell signal transduction. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…20,21 LGR5 is overexpressed in a variety of tumors, and its high expression level is associated with poor prognosis of various cancers, including colorectal, gastric, hepatocellular, and ovarian cancer. [22][23][24][25] Studies have shown that the increased expression of LGR5 occurs in the initial stage of EC development. With proliferation and growth of tumor epithelial cells, the expression of LGR5 becomes undetectable, likely because of the inhibitory effect of estrogen and progesterone on LGR5, suggesting LGR5 may be a biomarker for the diagnosis of early EC.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 LGR5 is overexpressed in a variety of tumors, and its high expression level is associated with poor prognosis of various cancers, including colorectal, gastric, hepatocellular, and ovarian cancer. [22][23][24][25] Studies have shown that the increased expression of LGR5 occurs in the initial stage of EC development. With proliferation and growth of tumor epithelial cells, the expression of LGR5 becomes undetectable, likely because of the inhibitory effect of estrogen and progesterone on LGR5, suggesting LGR5 may be a biomarker for the diagnosis of early EC.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between CSCs and Tregs further lead to tumor immunosuppression. Enriched LGR5 + LCSCs are associated with poor prognosis in HCC, whereas Tregs increased LGR5 of CSCs expression in gastric cancer through TGF-β1 [57][58][59] . Tregs and LGR5 + CSCs may also be associated in HCC.…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 98%
“…However, one subset of those hepatocytes, which is marked by leucine-rich repeat-containing Gprotein-coupled receptor 5 (LGR-5), was found to be involved in the HCC development 51 . Indeed, LGR-5 expression was found to be upregulated in HBV-related HCC tissues, and patients with higher expression of LGR-5 might have a poor outcome 52 . A very recent study seems to find out a link between LGR-5 and HCC initiation:…”
Section: Hbv-induced Hepatoma Cell Transformationmentioning
confidence: 99%